Throughput and Delay Analysis of an Underwater CSMA/CA Protocol with Multi-RTS and Multi-DATA Receptions. (8th May 2016) - Hwang, Ho Young; Cho, Ho-Shin
Abstract : We propose an underwater CSMA/CA protocol with multi-RTS and multi-DATA receptions using the long underwater propagation delay. We analyze the throughput and delay of the proposed underwater CSMA/CA protocol through a ring-based underwater network modeling. The proposed protocol does not need to maintain the information of internode propagation delay for each pair of underwater nodes. In the proposed protocol, when there are simultaneous transmissions of RTS frames from different underwater sensors to an underwater sink as their back-off counters reach zero, the sink can recover some RTS frames which are not overlapped at the sink in the time domain due to the long underwater propagation delay. Then, the sink transmits CTS frame containing the DATA transmission order and the IDs of the sensors which transmitted the recovered RTS frames. Sensors which correspond to the IDs contained by the CTS frame can transmit DATA frame to the sink according to the DATA transmission order. We evaluate the throughput and delay performance of the proposed protocol with varying the number of sensors and the contention window size compared to the conventional protocols. The analytical results agree with the simulation results well for the proposed protocol with various numbers of sensors and contention window sizes. The analytical and simulation results show that the proposed protocol outperforms the conventional protocols.